Wetter summers can intensify departures from natural variability in a warming climate - Colin R. Mahony (Nature Portfolio, 2018)
Climate change can drive local climates outside the range of their historical variability, straining the adaptive capacity of ecological communities. Here the authors show dependencies between climate variables can produce larger and earlier departures from natural variability than is detectable in individual variables.